2020
DOI: 10.1002/jor.24672
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus tears accelerate joint space loss and lateral meniscal extrusion increases risk of knee arthroplasty in middle‐aged adults

Abstract: We sought to use publicly available data from the Osteoarthritis Initiative (OAI), a multicenter prospective cohort study, to determine the rate of joint space loss and likelihood of knee arthroplasty due to magnetic resonance imaging (MRI)-diagnosed meniscal tears or meniscal extrusion in middle-aged adults with no to mild knee osteoarthritis. Participants (n = 2199; mean age, 60.2 years) with Kellgren-Lawrence osteoarthritis grades 2 (mild) (48.7%) or 0 to 1 (none) (51.3%) underwent knee MRIs at enrollment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Recently, some studies reported an association between lateral meniscal extrusion and knee OA. 14,31 Although DLM-reshaping surgery has shown good clinical outcomes in many previous studies, 40% to 50% of patients reported postoperative OA progression. 2,10 However, a few studies have investigated the relationship between DLM extrusion and knee articular cartilage degeneration.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, some studies reported an association between lateral meniscal extrusion and knee OA. 14,31 Although DLM-reshaping surgery has shown good clinical outcomes in many previous studies, 40% to 50% of patients reported postoperative OA progression. 2,10 However, a few studies have investigated the relationship between DLM extrusion and knee articular cartilage degeneration.…”
Section: Discussionmentioning
confidence: 98%
“…Medial meniscal extrusion progresses, resulting in knee OA changes 8,45,46,49 related to osteonecrosis. 14,39 Biomechanical in vivo studies have demonstrated that meniscal extrusion caused by a posterior root or radial tear results in a decreased tibiofemoral contact area and consequently increases the tibiofemoral contact pressure. 15,29,34 A medial meniscal extrusion of ≥3 mm was suggested to be pathological, 12,17,41 and this measurement is probably the most widely acknowledged cutoff value for research purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the several studies which have examined the association between quadriceps torque and radiographic TFJ structure following ACLR have been mixed [22,35]. As these studies used radiographs to measure TFJ structure, direct assessment of articular cartilage morphology was not possible and TFJ space narrowing measured by radiographs as reported by Tourville et al [35] is often secondary to meniscal extrusion rather than indicative of thinning of the articular cartilage [6]. The present study extended analysis of quadriceps strength to include functionally relevant, angle-speciic torque measurements and found that knee extension torque between 60° and 40° knee lexion explained 57-61% (inal covariate-adjusted models) of the variance in medial tibial cartilage volume.…”
Section: Discussionmentioning
confidence: 99%
“…Both ACL injury and meniscal lesions are known to increase the risk of osteoarthritis and subsequent TKA 8,[36][37][38][39][40] . In the present cartilage cohort, neither meniscal resection nor ACL surgery was associated with an increased risk of knee arthroplasty.…”
Section: Risk Of Arthroplastymentioning
confidence: 99%